2018
DOI: 10.1002/dc.24097
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective assessment of the effectiveness of the Milan system for reporting salivary gland cytology: A systematic review and meta‐analysis of published literature

Abstract: Introduction: Fine needle aspiration (FNA) has been widely utilized in establishing the nature of salivary gland lesions and guiding the clinical management. This study aimed to determine the accuracy of FNA in detecting salivary gland neoplasms and malignancies, employing the "Milan System for Reporting Salivary Gland Cytopathology" (MSRSGC).Method: A systematic search was conducted. The data on FNA and histologic diagnosis were extracted and categorized based on the MSRSGC and risk of malignancy (ROM) was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
77
6
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(101 citation statements)
references
References 113 publications
(146 reference statements)
16
77
6
2
Order By: Relevance
“…Our ROM findings are largely comparable to other such studies recently published in the literature, which report similar findings (Table including that of a large meta‐analysis of 92 studies. The calculated ROMs in our cohort appear to be on a par with those found in similar salivary gland studies in the current literature.…”
Section: Discussionsupporting
confidence: 92%
“…Our ROM findings are largely comparable to other such studies recently published in the literature, which report similar findings (Table including that of a large meta‐analysis of 92 studies. The calculated ROMs in our cohort appear to be on a par with those found in similar salivary gland studies in the current literature.…”
Section: Discussionsupporting
confidence: 92%
“…The three other cases which were suspicious for epithelial malignancy were finally diagnosed as non-neoplastic (myofibroblastic granuloma) or benign neoplasm (two PA). Though, the ROM for SM is consistent with the MSRSGC (68.8% vs. 60%) and with the literature (68,8% vs. 79%, 59%, 58%) [9,11,16].…”
Section: Discussionsupporting
confidence: 90%
“…The publication of papers analysing the role of the Milan System has further defined the ROM . In a recent study by Tommola et al, the non‐diagnostic category had a 0% ROM; however, a recent meta‐analytic study by Farahani analysed 92 studies including 16,456 SG‐FNA with surgical follow‐up The data from this study revealed a 7% ROM for the non‐diagnostic category based on 44 cases with histological follow‐up. The series also supported the statement that the non‐diagnostic rate should be <10%.…”
Section: Introductionmentioning
confidence: 92%
“…The series also supported the statement that the non‐diagnostic rate should be <10%. Nevertheless, the rate of non‐diagnostic FNA in the studies conducted at general hospitals was 21.28% ± 17.47% as compared to 4.38% ± 2.32% performed at referral or tertiary centres demonstrating an advantage for the latter group . The most common clinical management is represented by a repeat FNA with the use of ultrasound guidance and/or rapid on‐site evaluation in order to prevent a second non‐diagnostic result .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation